CLINICAL PRIVILIGE DAN TANGGUNG JAWAB DOKTER INTERNSIP DI RUMAH SAKIT - Kristanto, Erwin (Jurnal Biomedik : JBM, 2012)
Abstract: The internship program is a preregistration professional training program that has to be undertaken by each new graduate medical doctor, educated with a competence-based curriculum. After passing the competence test, the candidates for the internship program, whether civil servants or not, have to pesonally complete their application papers in order to start their professional training programs at the appointed medical health services, eg. a hospital. Since every hospital has different conditions, the medical comittee and the head of the hospital have to prepare the appropriate clinical privileges for the internship doctors. A good clinical appointment will protect the internship doctors while finishing their professional training, and also protect the hospital from any unnecessary risks. Keywords: internship program, clinical privilige. Abstrak: Program internsip adalah tahap pelatihan keprofesian pra-registrasi yang harus dijalani setiap dokter baru yang dididik dengan kurikulum berbasis kompetensi (KBK). Pasca kelulusan ujian kompetensi dokter Indonesia (UKDI), calon peserta internsip ikatan dinas maupun mandiri wajib mengurus kelengkapan administratif guna melaksanakan tugas keprofesiannya di sarana pelayanan kesehatan, salah satunya rumah sakit. Kondisi rumah sakit yang berbeda satu dengan yang lain, membuat komite medis bersama pimpinan rumah sakit harus membuat kajian clinical privilige yang tepat untuk para dokter internsip. Clinical appointment yang tepat akan melindungi dokter internsip dalam menyelesaikan pelatihan keprofesiannya, dan melindungi rumah sakit dari resiko hukum yang tidak perlu.Kata kunci: Program internsip, clinical privilige.